Gastro Intestinal Stromal Tumour: Treatment Strategies (Journal of Surgical Sciences, 2019)
Recent discoveries over the last decade have led to a greater insight to the molecular and biologicalbehavior of GIST along with its expression of receptors like KIT and platelet derived growthfactor. Consequently the advent of the tyrosine kinase inhibitor imatinibmesylate has been aphenomenal example of targeted molecular therapy. The unique success of the targeted therapyin the management of GIST has enhanced the multidisciplinary management approach to thedisease. Careful and intense study of the treatment strategies in GIST may lead to new era in themanagement of cancer.Journal of Surgical Sciences (2016) Vol. 20 (2) :55-58